Mechanical strength of wheat grain varieties influenced by moisture content and loading rate - Li, Yaoming; Chandio, Farman Ali; Ma, Zheng; Lakhiar, Imran Ali; Sahito, Abdul Razzaque; Ahmed, Fiaz; Mari, Irshad Ali; Farooq, Umer; Suleman, Muhammad (International Journal of Agricultural and Biological Engineering, 2018)
Mechanical shear resistance of wheat grain is a significant concern for the designers and researchers related to the design of threshing, handling and processing machinery of the field crops. The grain mechanical properties directly affect the machine geometry and its operational parameters. The present study was carried out to determine the shear resistance of five wheat varieties (Locally names; TD-02, Sindhu-1105, Benazir, China and SKD-118) influenced by moisture content (16.7%, 18.7% and 19.5%) and loading rate (3 mm/s, 6 mm/s and 9 mm/s). However, some physio-dimensional properties (length, width, thickness, slenderness ratio, surface area and sphericity) were obtained at different moisture contents. The results showed that the shear resistance reduced by increasing the moisture content and loading rate. The average shear resistance decreased from 10.45 N to 3.74 N for 3-9 mm/s loading rate at moisture content of 16.7% to 19.5%. Thus, the maximum correlation (r = 0.905) of shear resistance obtained at 16.7%, whereas minimum correlation (r = 0.692) obtained at 19.5%. The shear resistance of wheat grain was highly significant (p<0.05) at 9 mm/s for 19.5%. Shear resistance decreased with an increase in the moisture content in the grain whereas deformation is increasing with the increase of moisture content. However, the maximum bulk density of wheat grain obtained at 19.5% for SKD-118, while the minimum obtained at 16.7% for TD-02. It is recommended that the design and modification of wheat grain processing equipment should be executed on the physio-mechanical properties of grain varieties.Keywords: wheat grain, shear resistance, bulk density of grain varieties, moisture content, loading ratesDOI: 10.25165/j.ijabe.20181104.3737Citation: Li Y M, Chandio F A, Ma Z, Lakhiar I A, Sahito A R, Ahmad F, et al. Mechanical strength of wheat grain varieties influenced by moisture content and loading rate. Int J Agric & Biol Eng, 2018; 11(4): 52–57.